2006
DOI: 10.1590/s1519-69842006000200013
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural aspects of the intercellular bridges between female bee germ cells

Abstract: The germline cells in the ovary of the female bee are interconnected by intercellular bridges kept open by cytoskeletal reinforcements in the plasmic membrane. These bridges among the germline cells display a dynamic behavior and probably act in the determination of the oocyte among the cells of the clone formed by the premeiotic mitoses, subsequently forming a pathway that enables the products synthesized by the nurse cells to reach the oocyte during its maturation. The cytoskeletal elements in the intercellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Again, this location is consistent with the sites where ultrastructural studies have found the presence of microtubules (Patrício and Cruz-Landim, 2006;Staurengo-da-Cunha, 1988). The RNA that passes from the nucleus into the nurse cell cytoplasm through the nuclear pore and from one nurse cell the another until reach the oocyte.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Again, this location is consistent with the sites where ultrastructural studies have found the presence of microtubules (Patrício and Cruz-Landim, 2006;Staurengo-da-Cunha, 1988). The RNA that passes from the nucleus into the nurse cell cytoplasm through the nuclear pore and from one nurse cell the another until reach the oocyte.…”
Section: Discussionsupporting
confidence: 86%
“…The tubulin in the bridges may be the remains of mitotic spindle and therefore located in the fusome, as has been revealed in transmission electron microscopy images (Patrício and Cruz-Landim, 2006). Impaired development of fusome hinders oocyte growth (Cuevas et al, 1996;Hartfeler and Steinbück, 1997;Patrício and Cruz-Landim, 2006;Tanaka and Hartfelder, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations